1998
DOI: 10.1292/jvms.60.253
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Theileria Parasite Infection in Cattle in Taiwan.

Abstract: ABSTRACT. An survey of Theileria parasite infection in cattle in Taiwan was carried out by polymerase chain reaction (PCR). A total of 491 blood samples, 105 from southern area and 386 from northern area, were collected from bovine in 16 different farms. From northern area, Theileria piroplasms could be seen in only 4 of 105 blood samples microscopically. However, when p32/34 genes (encoding immunodominant piroplasm surface proteins) were amplified by PCR, 15 blood samples were detected positive. They were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Previously, one Okinawa isolate exhibited an SDS-PAGE protein profile similar to that of T. buffeli (Zakimi et al, unpublished data). According to epidemiological studies, I-type, rather than C-and Btype parasites, tends to be associated with clinical theileriosis [9,21]. However, no obvious correlations between MPSP types and clinical signs as measured by PCV were evident in this study, (data not shown).…”
contrasting
confidence: 66%
“…Previously, one Okinawa isolate exhibited an SDS-PAGE protein profile similar to that of T. buffeli (Zakimi et al, unpublished data). According to epidemiological studies, I-type, rather than C-and Btype parasites, tends to be associated with clinical theileriosis [9,21]. However, no obvious correlations between MPSP types and clinical signs as measured by PCV were evident in this study, (data not shown).…”
contrasting
confidence: 66%
“…Clinical infection can also result in decreased milk production in dairy cattle (7). T. orientalis is a conditional pathogen, and while pathogenic forms are largely limited to Eastern Asia and Australasia (5, 6, 8-10), it is frequently detected in asymptomatic animals; these benign forms are globally spread (5,(11)(12)(13)(14). Analysis of the most common genotyping locus (p32), encoding the variable major piroplasm surface protein (MPSP), currently identifies 11 distinct T. orientalis genotypes (13,15,16).…”
mentioning
confidence: 99%
“…The minority (14/28) was C-type parasites which were found as a mixed population with Thai-and B1-type parasites. Similarly, the Australian Italian and Taiwan benign Theileria parasites are also composed of B1-and C-type [17,23]. Nucleotide sequences of Australian C-type MPSP gene was similar to that of Japanese C-type parasite with 98.5% homology [11].…”
Section: Resultsmentioning
confidence: 99%